HR Professionals’ Effectiveness, Organizational Culture and High Performance Work System Link: Evidence from Pakistan - Fareed, Muhammad; Isa, Mohd Faizal Mohd; Mohd Noor, Wan Shakizah Wan (International Review of Management and Marketing, 2017)
HR professionals’ effectiveness is widely discussed as the most significant factor within the organization to gain sustainable competitive advantage at the present time. Nonetheless, the study investigates the impact of organizational culture on HR professionals’ effectiveness in telecom sector of Pakistan. Moreover, it also examines the moderating role of high performance work system in above mentioned correlation. A total of 75 survey questionnaires were distributed to HR managers of telecom firms, out of which 40 HR manager responded which makes 53.3% response rate. The study has used SmartPLS 3 for the assessment of the hypothesized model. The statistical results have established the strong positive effect of organizational culture on HR professionals’ effectiveness, however, findings reveal high performance work system doesn’t moderate this relationship. The study concludes organizations with strong organizational culture can achieve sustainable competitive advantage by augmenting HR professionals’ effectiveness, moreover, organizations have to align their HR strategies with robust HR system which can enhance HR professionals’ effectiveness. The findings of the study are of a great value to both theory and practice and have vital implications for academicians, practitioners and policy makers. Keywords: HR Professionals’ Effectiveness, Organizational Culture, High Performance Work System, Telecom, Pakistan, SEM-PLS JEL Classifications: D23, L20, O15